Strategy for Implementation of the Security Maturity Model in e-Government Systems in Indonesia - Tashia Indah Nastiti (Department of Electrical Engineering, 2022)
The security maturity level of Indonesia's e-Government system needs to be evaluated to determine the current status of security implementations and to plan for overall system security improvements. In general, the maturity model describes how a system consisting of humans and devices performs their duties. These capabilities include effective leadership and governance, level of awareness of implementers, and capabilities of existing tools. This study aims to create a strategy in implementing the security maturity model in the e-Government system in Indonesia. The research method uses a mix method, namely qualitative and quantitative methods. The qualitative method aims to obtain the Critical Success Factors Implementation of the security maturity model, and the quantitative method is used to analyze the results of the Critical success factor validation using SPSS. The strategy for the Security maturity model is based on the PDCA (Plan-Do-Check-Act) Model.